IL-1β is not critical to chronic heart dysfunction in mice with Chagas disease - Sousa Oliveira, Camila Victória; Moreno-Loaiza, Oscar; Figueiredo-Vanzan, Daniel; Peroba Ramos, Isalira; Mata-Santos, Hilton; Torres Bozza, Marcelo; Neto Paiva, Claudia; Medei, Emiliano (Frontiers in Immunology, 2022)
Long after Trypanosoma cruzi infection, 40% of individuals develop a progressive chronic chagasic cardiomyopathy (CCC), with systolic dysfunction and arrhythmias. Since we previously showed IL-1β mediates the development of systolic dysfunction and cardiac arrhythmias in diabetes mellitus and cardio-renal syndrome, and IL-1β remains elevated in Chagas disease patients, here we tested the role of IL-1β in CCC using a mouse model. Mice deficient in IL-1R expression (Il-1r-/-) survived acute T. cruzi infection with greater parasitemia than controls but did not lose weight as wild-type (WT) did. At the chronic stage, WT presented prolonged ventricular repolarization intervals (QJ), while Il-1r-/- presented intervals like non-infected controls. Infected Il-1r-/- and WT did not differ in stroke volume (SV), incidence of cardiac arrhythmias on electrocardiography (EKG), whole heart action potential duration (APD), or incidence of triggered activity after S1-S2 protocol, a measure of susceptibility to cardiac arrhythmias. We also treated chronically infected WT mice with an IL-1R antagonist, Anakinra. Treatment shortened the QJ interval but did not improve the SV or the incidence of cardiac arrhythmias on EKG. Anakinra failed to reduce triggered activity upon electrical extra stimulation protocol. In conclusion, the absence of a functional IL-1β/ IL-1R signaling did not prevent or reverse the decrease of SV or the incidence of cardiac arrhythmias induced by chronic T. cruzi infection, implying this is not a critical mechanism in generating or maintaining CCC. Since similar cardiac abnormalities were previously credited to IL-1β signaling, ruling out this mechanism is important to discourage further attempts of IL-1β blockade as a therapeutical measure.